Joint control of visually guided actions involves concordant increases in behavioural and neural coupling - David R. Painter (Nature Portfolio, 2021)
To examine how joint actions could be mediated in the absence of cues from a co-actor, Painter et al. performed neural recordings and eye tracking while pairs of participants guided a cursor either individually or together with a partner (joint control) from whom they were physically and visibly separated. They demonstrated that joint control involved increases in both behavioural and neural coupling, which were mediated by a neural offset response.